Net aboveground primary production and biomass dynamics of Schoenoplectus californicus (Cyperaceae) marshes growing under different hydrological conditions - Pratolongo, P. (2008)
We studied different functional attributes on two Schoenoplectus californicus (C. A. Mey) Sójak marshes that appear as very similar communities in terms of structure and dominant species, although they are settled on opposite ends along a fluvial-tidal gradient in the Lower Delta of the Paraná River. Obtained results showed a significantly higher net aboveground primary production (NAPP) in the marsh directly affected by tides (1999.41 ± 211.97 g m-2 year-1). In the upstream site, less prone to tidal flooding, S. californicus had a lower NAPP (1299.17 ± 179.48 g m-2 year-1) and the system showed a higher ability to keep the produced biomass within the marsh, with significantly higher amounts of standing dead biomass (1316.00 ± 336.01 vs. 112.40 ± 55.05 g m-2), as well as higher organic contents in soils (16.20 ± 0.12 % vs. 0.70 ± 0.08 %). Results of the present study suggest that high energy overland flows may change the marsh functioning from a stable system accumulating organic matter to an aggressively growing marsh with higher rates of mineral accumulation.